Quantifying the Influence of Leadership Styles on Faculty Motivation and Academic Innovation in Higher Education - Nur Haris Ependi; Didik Notosudjono; Eka Suhardi (Managere: Indonesian Journal of Educational Management, 2024)
The research aims to produce strategies and ways to improve lecturers' creativity through efforts to identify the magnitude of the direct and indirect influence of Transformational Leadership, Empowerment, Effectiveness and Utilization of ICT, and Work Motivation. This study uses a survey method and path analysis techniques, which are then subjected to SITOREM analysis. The population in the study amounted to 269 people, and a sample was taken randomly of 215 lecturers using the Taro Yamane formula. The results of the study prove that there is an influence of Transformational Leadership (by1 = 0.184), EmpowermentEmpowerment (by2 = 0.163), Effectiveness and Utilization of ICT (by3 = 0.275), and Work Motivation (by4 = 0.148) on Lecturer Creativity. SITOREM analysis proves that increasing creativity is done by improving weak indicators, namely the courage to take risks and work on complex things, developing or maintaining indicators of developing something new and different, providing problem-solving, and openness to new ideas. Transformational leadership is done by improving weak indicators, namely encouraging novelty, having charisma, having consideration, and providing inspiration. The implications of this research suggest that higher education institutions in Indonesia should prioritize the development of transformational leadership styles, empower faculty members, and invest in ICT tools to enhance work motivation, ultimately fostering a creative and innovative academic environment.